The establishment of a multiparty system in Turkey and its role in the country's socio-political life. - Boltaeva Mohichehra Jamshid kyzy; Farida Tuychievna Khaldibekova (Genius Publishing Group, 2022)
One of the main conditions of democratic life is the issue of multiparty system. A democratic society, of course, requires a multiparty system. Multipartyism is characterized, first of all, by the ability of any social stratum and group, regardless of their interests and views in society, to fully reflect their goals and aspirations. Each party, as a political force representing the interests of a certain segment of the population, expresses different interests and views. When they unite in pursuit of common goals, such as the homeland and the interests of the nation, they develop the life of the state and society in the shadow of the struggle of different opinions. Today, many countries in the guise of democracy are following this path. However, the process of transition to a multiparty system has taken place in different countries at different stages and with specific features
Keywords: Turkey; Republic; Union; Development Party